Cytomegalovirus in solid organ transplant recipients—Guidelines of the American Society of Transplantation Infectious Diseases Community of Practice. Issue 9 (28th March 2019) - Razonable, Raymund R.; Humar, Atul
Abstract: Cytomegalovirus (CMV) is one of the most common opportunistic infections that affect the outcome of solid organ transplantation. This updated guideline from the American Society of Transplantation Infectious Diseases Community of Practice provides evidence‐based and expert recommendations for screening, diagnosis, prevention, and treatment of CMV in solid organ transplant recipients. CMV serology to detect immunoglobulin G remains as the standard method for pretransplant screening of donors and transplant candidates. Antiviral prophylaxis and preemptive therapy are the mainstays of CMV prevention. The lack of a widely applicable viral load threshold for diagnosis and preemptive therapy is highlighted, as a result of variability of CMV nucleic acid testing, even in the contemporary era when calibrators are standardized. Valganciclovir and intravenous ganciclovir remain as drugs of choice for CMV management. Strategies for managing drug‐resistant CMV infection are presented. There is an increasing use of CMV‐specific cell‐mediated immune assays to stratify the risk of CMV infection after solid organ transplantation, but their role in optimizing CMV prevention and treatment efforts has yet to be demonstrated. Specific issues related to pediatric transplant recipients are discussed.